(untitled) (Jurnal Teknologi (Sciences & Engineering), 2016)
Conventional analysis and design of shallow foundation are based on the assumption that the soil is under fully saturated condition. However, shallow foundations are typically constructed near the ground surface where the soil is under partially saturated condition. Therefore, more research to investigate the behaviour of shallow foundation in unsaturated soil is very essential in order to aid engineers in making good analysis and design. This paper presents a series of laboratory footing tests conducted on unsaturated sandy soil. A specially designed test tank was fabricated for the test. Square footings of two different sizes (100 mm x 100 mm and 150 mm x150 mm) were used and loaded on Rawang sand which has residual suction value of 10 kPa. The measured values of matric suction of the soil in the test tank were in the range of 0 to 30 kPa. Based on the results, it was observed that bearing capacities of shallow foundation under fully saturated condition were the lowest compared to soil under unsaturated conditions. The highest values were measured at matric suction equals to residual suction (i.e 10 kPa). Furthermore, the relationship between the bearing capacities of shallow foundation with the matric suction was observed to be non-linear.Â Â Â